To Pester or Leave Alone: Lifetime Value Maximization through Optimal Communication Timing - Dreze, Xavier (Institutional Knowledge at Singapore Management University, 2003)
The marketing literature has long acknowledged the importance of a customer’s lifetime value in customer relationship management. More recently, researchers have turned their attention to the links between satisfaction and both customer acquisition and retention strategies. In this paper, we are interested in understanding the impact of communication frequency on customer retention and ultimately on lifetime value. We develop a theoretical framework for managing a customer database and addressing the tradeoffs between value extraction and customer retention. An empirical application of this framework is conducted for permission-based email marketing in the entertainment industry. This application recognizes the customization ability underlying one-to-one marketing, and yields decision rules for how a firm should interact with individual customers. We find that inter-communication time has a dramatic impact on customer behavior. It affects both attrition and consumer surplus and thus has a critical impact on the value of a customer database. This impact is asymmetric, thus managers are advised to err on the side of longer rather than shorter inter-communication times. We further find that retention raises the value of a customer database in two ways. First, one can only derive revenue from customers who are active. Second, we demonstrate that the larger a firm’s customer base, the lower its per-customer contact costs. These findings are supported by our empirical analysis.